Community Empowerment on Establishment of Friendly-Village for Women and Children: Series of Agendas on Legal Protection and Community Empowerment in Bandungan Sub-District, Bandungan District, Semarang Regency - Sarno Setiawan; Muhammad Afis Saifunuha; Jauza Lasta Kautsar; Cahya Wulandari (Universitas Negeri Semarang, 2019)
Worthy children and women's Village/Sub-district is a village/sub-district development that brings together the commitment and resources of village/village government that involve the community and business world in the sub-district in order to promote, protect, Fulfilling and respecting the rights of children and women, which are planned consciously and sustainably. Some laws have been established to support the protection of children and women such as the Act of the Republic of Indonesia number 35 year 2014 about the amendment to law Number 23 year 2002 about protection Children and Law Number 23 year 2004 concerning the elimination of violence in households. In order to realize the child and women's friendly villages, there are several efforts that can be done as the socialization of legal protection and community empowerment. Socialization programs not only provide information or knowledge but also supported by the empowerment of community that provides training and experience in the community. So that socialization tends to only provide information to be easier to understand by the community through the Community Empowerment program and increase public awareness to continue to actively participate in the realization of child and women's friendly villages.